Splenic phagocytic function in patients with inflammatory bowel disease. - Jewell, D; Berney, J; Pettit, J (Informa Healthcare, 1981)
Splenic phagocytic function has been assessed in patients with inflammatory bowel disease. No Howell-Jolly bodies were found on blood film examination. Slow clearance times of heat damaged red cells were found in 13 of 16 patients with ulcerative colitis compared with 4 of 17 patients with Crohn's disease (P less than 0.01). For ulcerative colitis prolonged clearance times were strongly related to the length of history (r = 0.90; P less than 0.01). The prolongation of half-clearance times correlated poorly with splenic size suggesting a functional impairment of the reticuloendothelial system.